Eco-mysticism in Pablo Neruda’s selected poetry - Khosravi, Goltaj David; Sistani, Roohollah Reesi; Raihanah M.M.,; Ravichandran Vengadasamy, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Eco-poetry as a modern literary theory is a branch of ecocriticism which focuses on the relationship between man and the physical world. Using the Latin American Nobel Prize winner Pablo Neruda’s selected poetry, this paper sets out to explore the themes of mystical and spiritual consciousness through eco-poetical evidence. This study utilizes the theoretical framework of eco-poetry to illuminate the dual ecological and mystical phenomenon, both in its theoretical and literary context. The thematic analysis of the study emphasizes the mystical and ecological spirituality or eco-mysticism of Neruda’s poetry. The finding indicates that Neruda’s poetries demonstrate man’s interdependence and spiritual interconnectedness with his environment. The finding also signals Neruda’s poetic quest of focusing on the significance of nature and poetry as a means for finding spirituality in the physical world.